Dry Sliding Wear Behaviour of Rheocat Al-5.7si-2cu-0.3mg Alloy - A. Abdelgnei, M; Z. Omar, M; J. Ghazali, M; A. Gebril, Mohamed; N. Mohammed, M (International Journal of Engineering and Technology, 2018)
In this study, the effect of improved microstructure of Al-5.7Si-2Cu-0.3Mg alloys by using semisolid process on hardness and dry sliding wear behaviour were investigated. The microstructures of conventional cast alloy were totally dendritic, while in rheocasting the dendritic transfer to fine globular microstructures after using cooling slope casting. Tribological tests were carried out by using a pin-on-disc apparatus in dry sliding conditions. Wear tests were at low sliding speed 1ms-1 ,applied load at 50N and three different sliding distance (i.e., 1.8Km, 5.4Km and 9Km) respectively. An optical microscope and a scanning electron microscope were used to examine the microstructure and to understand the wear mechanism on the worn surface of both samples. The results showed that, the wear resistance of rheocast alloy was improved and higher than that those produce by conventional casting. The volume loss of rheocast alloy show reduction more than 18% at 1.8Km and 10% at 9Km compared to as-cast alloy. Moderate wear regimes were appeared in both alloys, according to the range of wear rate. The friction coefficient had increased due to increase in the contact point between pin and disc materials. The dominant wear mechanism for conventional and rheocasting alloys was adhesion wear and abrasive wear respectively.Â Â